Regioselective synthesis of benzannulated [5,6]-oxaspirolactones via Cu(II)-catalyzed cycloisomerization of 2-(5-Hydroxyalkynyl)benzoates - Thorat, Sagar S.; Shimpi, Sagar P.; Sambherao, Pooja I.; Krishna, Gamidi Rama; Kontham, Ravindar (Journal of Organic Chemistry, 2023)
Spiroketals and oxaspirolactones are widely found in biologically active natural products, serving as important structural motifs. In this study, we present a Cu-(II)-catalyzed cascade cycloisomerization of 2-(5-hydroxyalkynyl)-benzoates, enabling the regioselective synthesis of benzannulated [5,6]-oxaspirolactones containing an isochromen-1-one moiety. This strategy offers a rapid and efficient approach to access a diverse array of benzannulated [5,6]-oxaspirolactones. The methodology presented here showcases a broad substrate scope, delivering good yields and scalability up to gram scale. The structures of the oxaspirolactones were unequivocally confirmed through single-crystal X-ray analysis and by analogy using H-1 and C-13-H-1 NMR data.
Keywords: Construction; Isocumarins; Strategies

Bi(OTf)3-promoted cascade annulation of hydroxy-pyranones and unsaturated γ-ketoesters for the construction of polycyclic bridged pyrano-furopyranones - Rathod, Akshay B.; Borade, Balasaheb R.; Sambherao, Pooja I.; Kontham, Ravindar (Organic and biomolecular chemistry, 2024)
An efficient protocol for constructing complex three dimensional polycyclic bridged chromano-furopyranones and pyrano-furopyranones (closely related to bioactive natural products) via bismuth(III)-catalyzed cascade annulation of hydroxy-pyranones and unsaturated gamma-ketoesters is presented. This process involves intermolecular Michael addition, intramolecular hemiketalization, lactonization, formation of one C-C bond and two C-O bonds, rings, and contiguous stereocenters.
Keywords: 1 3-Dicarbonyl Compounds; alkynols; Coumarins; Fungus

Divergent access to polycyclic spiro- and fused-N,O-ketals through Bi(OTf)3-catalyzed [4+2]-annulation of cyclic N-sulfonyl ketimines and alkynols - Nakate, Ashwini K.; Kataria, Priyanka; Sambherao, Pooja I.; Krishna, Gamidi Rama; Kontham, Ravindar (Chemical Communications, 2024)
Bismuth(iii) triflate-catalyzed [4+2]-annulation of cyclic N-sulfonyl ketimines (derived from saccharin) and alkynyl alcohols (4-pentyn-1-ols and 5-hexyn-1-ols) has been reported. This cascade annulation provides a diverse array of polycyclic spiro-and-fused N,O-ketals with excellent substrate scope, good isolated yields, and diastereoselectivities under mild reaction conditions.